Diagnóstico de la salud y seguridad del trabajo en la asociación de emprendedores agropecuarios “San Sebastián” parroquia Guaytacama, cantón Latacunga, provincia de Cotopaxi 2021 - López Rodríguez, Josselyn Elizabeth (2021)
The present work was carried out in the Association of Agricultural Entrepreneurs "San Sebastián", in the Parish of Guaytacama, emphasizing the diagnosis of health and safety at work (OSH) applied to the members of the association, the main objective was to diagnose the incidence of occupational risks in the health of the members of the Association of Agricultural Entrepreneurs "San Sebastián" Parroquia Guaytacama, Canton Latacunga, Province of Cotopaxi 2021, for which a survey was applied based on socio-economic and risk indicators which allowed characterize the farmer and his health problems, in which the results obtained show that 91.7% of the members are almost always exposed to physical risk factors such as heat, cold, solar rays, in the same way 100% are persistently exposed to biological factors such as: mosquito bites; Among other indicators evaluated, in safety risks more than 80% had accidents and conditions in their workplace, such as: cuts, blows, among others, and through these there are serious consequences of musculoskeletal discomfort. In addition, indicators on COVID-19 were established, since being an issue of great importance through which we are currently going through, the results of the level of exposure of this indicator were favorable since 100% of the partners have not contracted the virus and find a low risk of contagion in their production units.